Pola Pembinaan Ketrampilan Shalat Anak dalam Islam - Mujiburrahman Mujiburrahman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Coaching skills are very important for children to pray, because prayer is actually going to make children pious and awake from shameful and unjust deeds. Coaching prayer right against children devastating for a child to an adult, if this is not observed, then the practice of prayer is wrong will be done by a child. As a result, children are always the fault in the prayers. Further development of this prayer is the responsibility of educators, especially parents and other educators who have received the trust of children. The pattern of guidance that should be done by educators; First, At-Ta'rif (Introducing), educators have an obligation to introduce prayer, so that in the future children feel strange when I hear the words of the prayer, however, is a human child whose age is different from adults, so in this case the child is very need guidance in recognizing the prayer and the things relating to prayer. After receiving guidance, the child is expected to know that prayer is an obligation that should be are conducted by every Muslim. Second, approach. Among others; a) provoking the spirit of competent children, b) awaken the fear of a child of God, c) reminding them of the virtues perform ablutions, d) strive to always be able to be an example of good role model for children, e) to wake them for work on the morning prayer, f) give attention to familiarize the children daughter prayers at home.